Forgoing Life-Sustaining or Death-Prolonging Therapy in the Pediatric ICU - Devictor, D.; Latour, Jos; Tissières, P. (2008)
Most deaths in the pediatric intensive care unit occur after a decision to withhold or withdraw life-sustaining treatments. The management of children at the end of life can be divided into three steps. The first concerns the decision-making process. The second concerns the actions taken once a decision has been made to forego life-sustaining treatments. The third regards the evaluation of the decision and its implementation. The mission of pediatric intensive care has expanded to provide the best possible care to dying children and their families. Improving the quality of care received by dying children remains an ongoing challenge for every pediatric intensive care unit team member. © 2008 Elsevier Inc. All rights reserved.